The Effectiveness of Advertising by Using Social Media - Immie Rozianie Abd Rahim; Diyana Nur Norazman (Human Sustainability Procedia, 2022)
This study aimed to investigate the effectiveness of advertising by using social media. The findings of this study will represent the factor that contributes to the effectiveness of the advertising method such as the market expense, target audience, and flexibility. Quantitative methods were applied in this study and data were collected through the distribution of questionnaires to 120 respondents who are employees of Berjaya Starbucks Coffee. In addition, the findings showed a significant relationship between social media and social media advertising. The study also found that many people prefer social media as an advertising medium. It is also found that social media is a good medium to use for advertisement because it is quick and budget-friendly. Social media has been proved as a better medium compared to traditional Media. Hence, this study contributes to the field of communication through the establishment of a more comprehensive variable related to social media in advertising.